Problem of Career Counseling Management in School During the Covid 19 Pandemic - silvianetri silvianetri; Irman Irman; Che Zarrina Saari; Zubaidah Zubaidah; Putri Yeni (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
The main problem of career counseling in schools during the COVID-19 pandemic is management problems. The purpose of this study is to reveal data related to career management problems in schools during the covid 19 period. The research uses a qualitative approach, especially phenomenology. The research respondents consisted of Guidance and Counseling teachers, school principals, vice principals and students of SMA N Padang City. Research data obtained through interviews and observations. Researchers used data triangulation to test the validity of the data, especially source triangulation. The data is analyzed based on the theory of Miles and Huberman. The results of the study revealed that; 1) unrealistic planning of career counseling services and the absence of online counseling designs. 2) the organization of career counseling services that are not in accordance with the guidelines, 3) the implementation of career counseling services that are not in accordance with the student's traits and are incidental in nature, and 4) controlling and supervising the implementation of career counseling that has not been maximized by the principal. The conclusion of the research is that career management problems in schools are related to planning, organizing, implementing and controlling.